The Influence of Islamic Leadership on Employee Performance with Intrinsic and Extrinsic Motivation as Intervening Variables : Study at PT. Bank Muamalat Indonesia, Tbk Malang Branch and Batu Sub-Branch - Mubarok, Ahmad Zaki; Siswanto, Siswanto (Universitas Islam Kadiri, 2024)
In the years 2020-2021, PT. Bank Muamalat Indonesia, Tbk experienced a decline in employee performance by 0.37%, which potentially has significant implications for the sustainability of the banking institution. To address this issue, the bank needs to implement appropriate strategies to enhance intrinsic and extrinsic motivation among employees. With increased intrinsic and extrinsic motivation, it is anticipated that employees will be more motivated to improve their performance. The importance of building intrinsic and extrinsic motivation among employees aligns with the values of Islamic leadership. Therefore, this research aims to analyze the direct and indirect effects of Islamic leadership on employee performance at PT. Bank Muamalat Indonesia, Tbk in KC Malang and KCP Batu. Using a quantitative approach, the study involves 45 employees as the population from PT. Bank Muamalat Indonesia, Tbk in KC Malang and KCP Batu. Data collection is conducted through questionnaires, and hypothesis analysis employs the Structural Equation Model (SEM) based on Partial Least Squares (PLS) using the SmartPLS 4 application. The research findings indicate that extrinsic motivation significantly influences employee performance. Islamic leadership also has a positive effect on intrinsic and extrinsic motivation. Furthermore, extrinsic motivation plays a mediating role in mediating the influence of Islamic leadership on employee performance. Thus, the application of Islamic leadership values can be an effective strategy in enhancing employee performance in the Islamic banking environment